Giant Ulcerative Dermatofibroma - Karlidag, Turgut; Keles, Erol; Orhan, Israfil; Kaplama, Mehmet Erkan; Cobanoglu, Bengu (Hindawi Ltd, 2013)
Dermatofibroma is a slowly growing common benign cutaneous tumor characterized by hard papules and nodules. The rarely seen erosions and ulcerations may cause difficulties in the diagnosis. Dermatofibrosarcoma protuberans, which is clinically and histopathologically of malignant character, displays difficulties in the diagnosis since it has similarities with basal cell carcinoma, epidermoid carcinoma, and sarcomas. Head and neck involvement is very rare. In this study, a giant dermatofibroma case, which is histopathologically, ulcerative dermatofibroma, the biggest lesion of the head and neck region and seen rarely in the literature that has characteristics similar to dermatofibrosarcoma protuberans, has been presented.